SURGICAL TREATMENT OF MEDICATION-RELATED OSTEONECROSIS OF THE JAW USING PLATELET-RICH FIBRIN: A RETROSPECTIVE CLINICAL ANALYSIS (American Journal of Interdisciplinary Research and Development, 2026)
Medication-related osteonecrosis of the jaw (MRONJ) is a severe complication of antiresorptive and antiangiogenic therapy characterized by drug-induced damage to the jawbone in the absence of prior radiation therapy or metastatic disease. The unpredictability of treatment outcomes necessitates the search for approaches capable of enhancing tissue repair. The aim of this study was a retrospective evaluation of the effectiveness of surgical treatment of MRONJ with and without the use of platelet-rich fibrin. Data from 42 patients with mandibular osteonecrosis treated between 2022 and 2026 were analyzed; patients were divided into two groups according to PRF use. Clinical healing was considered the primary outcome measure. Favorable outcomes were observed in approximately 64% of cases. The use of PRF demonstrated a tendency toward improved treatment results without reaching statistical significance, indicating the need for further